Effectiveness of Spinal Stabilization Exercises on Movement Performance in Adults with Chronic Low Back Pain - Khalid Alkhathami; Yousef Alshehre; Kelli Brizzolara; Mark Weber; Sharon Wang-Price (North American Sports Medicine Institute, 2023)
# Introduction Low back pain (LBP) is a musculoskeletal disorder that affects more than 80% of people in the United States at least once in their lifetime. LBP is one of the most common complaints prompting individuals to seek medical care. The purpose of this study was to determine the effects of spinal stabilization exercises (SSEs) on movement performance, pain intensity, and disability level in adults with chronic low back pain (CLBP). # Methods Forty participants, 20 in each group, with CLBP were recruited and randomly allocated into one of two interventions: SSEs and general exercises (GEs). All participants received their assigned intervention under supervision one to two times per week for the first four weeks and then were asked to continue their program at home for another four weeks. Outcome measures were collected at baseline, two weeks, four weeks, and eight weeks, including the Functional Movement Screen^TM^ (FMS^TM^), Numeric Pain Rating Scale (NPRS), and Modified Oswestry Low Back Pain Disability Questionnaire (OSW) scores. # Results There was a significant interaction for the FMSTM scores (_p_ = 0.016), but not for the NPRS and OSW scores. Post hoc analysis showed significant between-group differences between baseline and four weeks (_p_ = 0.005) and between baseline and eight weeks (_p_ = 0.026) favor SSEs over GEs. Further, the results demonstrated that all participants, regardless of group, had significant improvements in movement performance, pain intensity, and disability level over time. # Conclusion The results of the study favor SSEs over GEs in improving movement performance for individuals with CLBP, specifically after four weeks of the supervised SSE program.